Features of intensive organ-sparing therapy for massive postpartum hemorrhage - V. A. Kramarskiy; I. V. Ezhova; N. L. Sverkunova; V. N. Dudakova (Acta Biomedica Scientifica, 2016)
Bleeding in pregnancy, childbirth and the postpartum period is one of the leading causes of maternal morbidity and mortality worldwide. There is no doubt that obstetric bleeding demands the development of improved methods for its diagnostics and treatment. We assessed the effectiveness of the treatment strategy for massive postpartum hemorrhage (PPH) with preservation of reproductive function, applied in the Perinatal Center of Irkutsk. We performed a retrospective analysis of 24 delivery cases, complicated by massive bleeding and successfully treated with preservation of reproductive organs. The massive nature of bleeding (> 30 % of blood volume) was registered in 15 (62.5 %) cases, mild (> 20 % but